Comparison of the offensive action in water polo games with the old and new rules - Platanou, T.; Grasso, G.; Cufino, B.; Giannouris, Y. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In 2005, the World Swimming Federation (FINA) changed the water polo rules to make the game more offensive. The most important changes were a) the game duration which changed from 7 to 8 min each period, and b) the period for keeping the ball which changed from 35 to 30 sec. According to the above mentioned alterations the game duration increased by 14,29% and the ball keeping period reduced by 14.29%. The aim of the present study was to examine the changes in offensive action as a result of the alterations in the above mentioned rules. For this purpose OMEGA`S statistical data from the 2004 Olympics and those of the LEN`S statistical team in the Belgrade European Championship in 2006 were used. The offensive actions in games played with the different rules were counted and compared in the final phase of a) the 2004 Olympics played with the old rules and b) the 2006 European Championship played with the new rules. The comparison was made for 1) shoot and goal 2) exclusion won 3) penalties won. A comparison of the position and the way of achievement was also performed for the shoot and goal. These were: a) from the periphery, b) from the center, c) from 5 or 7 m d) with extra man, e) from counter attack f) penalty. The mean findings were: a) in total, greater number of shoot (27±4 vs. 22±4) and goals (10±3 vs. 7±3) are performed from each team with the new rules (p<0.001). However, there is no statistically significant difference in, a) the number of goals per shoot and b) no difference exist in the number of exclusion and penalties with the new rules. Regarding the position from which the shoots were executed and the goals were performed, the analysis showed that the number of shoots from the periphery is greater with the new rules (10±3 vs. 7±2, p<0.001), but not the goals. For the extra man, a greater number of shoots (9±3 vs. 5.6±3.0, p<0.001) and goals (4±1 vs. 2±1, p<0.001) are performed with the new rules. In this as well as in all other situations, no difference was found in the number of goals per shoot, between the new and the old rules. In conclusion, it seems that although the number of offensive actions might be increased with the new rules, as a result of the extended game duration and the shortened time of keeping the ball, there was no change in the percent (the rhythm)